QUALITY INDICATORS FOR SPECIAL MILITARY SHOES - MYKHAILOVSKA, OKSANA; NADOPTA, TETYANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article examines concepts and quality categories of footwear products, in particular, for special military footwear.The classification of quality indicators of special military footwear was developed using the facet method of feature distribution. Consumer indicators, which, in turn, are divided into ergonomic and operational characteristics, include the following qualitative characteristics of quality indicators: anthropometric, hygienic, reliability, production performance. Production and economic indicators characterize the technological and economic support for the production of special military footwear.The proposed classification of quality indicators of special military footwear allows to fully cover the structure of the footwear design process, taking into account the anatomical and morphological features of the feet, ensuring comfort and protection of the feet from the effects of the external environment, using modern material packages. At the same time, the level of productivity of the shoe manufacturing process increases and maximum economic efficiency is ensured.
Keywords: special shoes; comfortable shoes; quality; quality indicators; consumer properties; production and economic indicators; reliability